On the phylogeny of Paleogene planktonic foraminifera: wall texture structure and a new genus name for the broedermanni lineage - D.M. Soldan; M.R. Petrizzo; I. Premoli Silva (2013)
The broedermanni lineage has been traditionally placed in the genus Igorina (see Berggren and others, 2006) being characterized by possessing a biconvex globorotaliid morphology, subglobular to subquadrate chambers, and by having a nonspinose wall texture with thin muricae on the test surface. Our analysis of specimens from the Pacific Ocean (ODP Leg 198, Shatsky Rise and ODP Leg 143, Alllison Guyot) suggest that the broedermanni group is phylogenetically related to Acarinina as the calcite structures of the wall are similar to the muricae rather than to the short pustules of the Paleocene igorinids (i. e., I. pusilla, I. albeari). In particular, the oldest species lodoensis shows a typical coarse muricate test similar to Acarinina while in its descendants, broedermanni and anapetes, the muricae are finer on the spiral side, and heavier muricae are developed only around the umbilicus. Moreover, in the broedermanni group the shell is not encrusted as in Igorina because the pustules remained isolated and increased in size to become thick muricae. The analysis of the pore structure in cross section seems to confirm the similarities and affinities between the wall texture of the broedermanni group and Acarinina. Both show an hourglass shape of the pores that become narrow in the outer calcite layer whereas in Igorina species the pores are tight in the inner calcite layer. In addition, the results from parsimony analysis (Soldan and other, 2011) confirm that the broedermanni group evolved in the late Paleocene/early Eocene from the group of round acarininids (A. mckannai and A. soldadoensis). The new genus Pearsonites (named in honor of Professor Paul N. Pearson) with Pearsonites broedermanni as type species, is here proposed to accommodate the early-middle Eocene globorotaliid taxa of the broedermanni lineage with a wall texture bearing muricae. Three species previously considered morphologically and evolutionary related to the Paleocene genus Igorina are here included in Pearsonites nov. gen., P. lodoensis, P. ...